2023
DOI: 10.1136/bmjopen-2022-061647
|View full text |Cite
|
Sign up to set email alerts
|

Role of social capital in response to and recovery from the first wave of COVID-19 in Thailand: a qualitative study

Abstract: ObjectiveThis study assesses the role of social capital among people and communities in response to the first wave of the pandemic in 2020.DesignQualitative study using focus group discussions.SettingCapital city (Bangkok) and the four regions (north, northeast, south and central) of Thailand.Participants161 participants of 19 focus groups with diverse backgrounds in terms of gender, profession, education and geography (urban/rural; regions). They are selected for different levels of impact from the pandemic.F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 48 publications
3
22
1
Order By: Relevance
“…Similar scenarios were reported in countries with similar dramatic deterioration of the socioeconomic situation, such as the neighbor Lebanon 10 . The shift to public sector hospitals intensi ed the needs and created further shortages in supplies and personnel, which resulted in exaggerated mortality rates during hospitalization 21 . As a result, public fear increased, and the motivation to present to emergency rooms diminished, creating a preference for home visits 10 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar scenarios were reported in countries with similar dramatic deterioration of the socioeconomic situation, such as the neighbor Lebanon 10 . The shift to public sector hospitals intensi ed the needs and created further shortages in supplies and personnel, which resulted in exaggerated mortality rates during hospitalization 21 . As a result, public fear increased, and the motivation to present to emergency rooms diminished, creating a preference for home visits 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this issue should not affect the overall robustness of our ndings for three reasons. First, diagnostic tests were also not available for a signi cant proportion of hospitalized patients in Damascus public hospitals due to a shortage of supplies and poor coordination between COVID-19 centers 21 . Second, mortality and respiratory failure rates were not signi cantly different between patients who were diagnosed based on the polymerase chain reaction (PCR) gold standard and those who were admitted merely based on their clinical presentation 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, social capital is a more attractive analytic tool to the World Bank and other multilateral institutions interested in community projects such as eradicating poverty (Prakash, 2010). For similar reasons, social capital rather than the social network has been frequently used in recent studies of how communities respond to and recover from the COVID-19 pandemic (e.g., Samutachak et al, 2023). A survey of seven European countries has found that a one-standard-deviation increase in social capital led to between 14% and 34% fewer COVID-19 cases per capita accumulated from mid-March until the end of June 2020, as well as between 6% and 35% fewer excess deaths per capita (Bartscher et al, 2021).…”
Section: Cultivating and Maintaining Social Network For Positive Ageingmentioning
confidence: 99%